Comparison of 18F-FDG positron mission tomography and computed tomography in patients with colorectal carcinoma and lymphoma : our initial clinical experience - Coha, Božena (Array, 2009)
Usporedili smo nalaze fluoro-18-fluorodeoksiglukoza (FDG) pozitronske emisijske tomografije (18F-FDG PET) i kompjutorizirane tomografije (CT) u bolesnika s malignim limfomom i kolorektalnim karcinomom